1997
DOI: 10.17660/actahortic.1997.448.25
|View full text |Cite
|
Sign up to set email alerts
|

Differential Assimilation of Nutrients in Paclobutrazol-Treated Peach Trees

Abstract: Paclobutrazol (Pbz) is a triazol that effectively inhibits vegetative growth in peach. Changes in mineral element concentration have been generally found. However, uneven distribution of the elements in the soil may partially account for these differences. To ascertain these effects, an experiment was designed under controlled conditions, in which sugar beet, used as a model plant, was grown hidroponically, treated with Pbz and the results compared to those from unbearing peach trees grown in the open. The bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
1
3
1
Order By: Relevance
“…Anusuya and Selvarajan (2014) discovered that the application of paclobutrazol increased the content of leaf nutrients at all stages of mango tree development. These results are in agreement with the findings of Atkinson and Crisp (1983) in apple rootstocks, Wang et al, (1985) in pears, and Pequerul et al, (1997) in peaches. Moreover, Singh et al, (2005)observed that soil application of paclobutrazol over two consecutive years increased the levels of P, K, and Ca in mango.…”
Section: Residual Effect Of Paclobutrazol On Leaf Nutrient Contentsupporting
confidence: 92%
“…Anusuya and Selvarajan (2014) discovered that the application of paclobutrazol increased the content of leaf nutrients at all stages of mango tree development. These results are in agreement with the findings of Atkinson and Crisp (1983) in apple rootstocks, Wang et al, (1985) in pears, and Pequerul et al, (1997) in peaches. Moreover, Singh et al, (2005)observed that soil application of paclobutrazol over two consecutive years increased the levels of P, K, and Ca in mango.…”
Section: Residual Effect Of Paclobutrazol On Leaf Nutrient Contentsupporting
confidence: 92%
“…Matsoukis et al 11 reported that Fe increased in lantana plants treated with similar sprayed PBZ concentrations (50 and 100 mg l -1 ) at the same SLs as in our study. Increased leaf Fe and Mn contents have been reported in Prunus persica L. Batch trees after treatments with lower drenched-applied PBZ concentrations 10 than those of our study.…”
Section: Resultscontrasting
confidence: 50%
“…Shading above plant canopies can alter light availability 8,9 and environmental conditions, thus influencing plant nutrition 10 . Consequently, the present work aims mainly to investigate the hypothesis of the different Fe and Mn response of lantana plants to different drenched-applied PBZ concentrations and light regimes.…”
Section: Introductionmentioning
confidence: 99%
“…The vertical bar at the right is the standard error of the analysis. in peach (Prunus persica [L.] Batsch) trees (Pequerel et al, 1997) as well as to increase or not (Wieland and Wample, 1985) the leaf concentration of this nutrient in potted apple (Malus domestica Borkh. 'Topred Delicious') plants compared to controls (0 mg ai) under glasshouse conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Light availability can be changed by the use of shading materials above plant canopies, causing thus a change in environmental conditions which has been reported to having an effect on plant nutrition (Pequerel et al, 1997). The use of shading materials above plants in glasshouses in the summer period in countries characterized by high values of solar radiation e.g.…”
Section: Introductionmentioning
confidence: 99%